Pelatihan dan Pendampingan Kepada Pengawas Menelan Obat (PMO) dalam Upaya Meningkatkan Kepatuhan Pengobatan Pasien Tuberkulosis di Puskesmas Haliwen - Usfinit, Paskalis Malafu; Olo, Annita; Akoit, Handrianus (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Pulmonary tuberculosis can cause serious problems and even death in people who have been infected with the mycobacterium tuberculosis bacteria. Tuberculosis patients will usually undergo treatment for a long time. Patients will get a treatment period of approximately 6 to 9 months. As a result of this long period of treatment, there are many cases reported that TB patients do not take medicine regularly, drop out of taking medicine, patients who have received medicine but are lazy to complete treatment for up to 6 months, already feel healthy finally drop out of treatment and family lacks support in completing treatment. Tuberculosis patients who are on medication need someone to always supervise and educate them. This person is usually called a Medication Swallowing Supervisor. Drug swallowing supervisors can come from family members, neighbors or the general public who have volunteered to help TB patients. PMO who come from the general public must be given training so that they have basic knowledge and skills in communication and negotiation so that they can convince TB patients and their families to take the correct treatment and complete treatment. This service method is in the form of training and mentoring which is carried out in several stages, namely preparation, implementation and sustainability of the program. The results of the pre and post tests on all trainees showed an increase in the ability of the trainees.